Sterben mit Anspruch? Sterbehilfe aus gesellschaftstheoretischer und historischer Sicht - Duncker, Simon; Schmidt, Almuth-Maria (Zeitgenössische Diskurse des Politischen, 2023)
This anthology aims to address a void in the debates on assisted dying and assisted suicide, which are dominated by legal, medical, theological and practical-ethical perspectives. Liberal institutionalisation of assisted suicide has been within reach since the Federal Constitutional Court's 2020 ruling. The existential questions of determining and shaping a good life and death touched upon in this ruling challenge a democratic society to engage in political self-understanding. Is it not up to historically and socio-theoretically informed voices to conceptualise the historical upheaval critically in order to argue for an emancipatory perspective? This book is an attempt at such a conversation in six contributions. With contributions by Simon Duncker, PD Dr. Stefanie Graefe, Dr. Robin Iltzsche, Prof. Dr. Thomas Macho, Dr. Angelika Pillen und Dr. Nina Streeck.